Calculation of thermal solid plate heating in conditions of theoretical counterflow - V. I. Timoshpolsky; J. S. Postolnik; S. M. Kozlov; I. A. Trusova; P. E. Ratnikov (Литьë и металлургия, 2001)
А mathematical model of thermal solid plate heating in conditions of theoretical counterflow^ is worked out. The analysis is given of heating dynamics at various values of ratio of water equivalents of metal and gas.